Method based on digital image correlation for damage assessment in masonry structures. (1st March 2015) - Nghiem, Huu-Luyen; Al Heib, Marwan; Emeriault, Fabrice
Highlights: A new approach is proposed for evaluating damage in masonry structures. A damage indicator associated with the total length of cracks is proposed. The relevance of the damage indicator is compared with usual global criteria. Monte Carlo simulations are used for estimating the measurement error. Application is given for damage assessment of masonry due to ground subsidence. Abstract: This paper presents a new approach based on the digital image correlation (DIC) technique for evaluating damage in masonry structures on the basis of the opening of joints. An application is proposed on experiments that are performed using a large-scale physical model reproducing both the soil-structure interaction and the masonry structure. Displacement fields of blocks obtained by DIC analysis are described in a new Discrete Element System (DES) where cracks appear near joints with openings between blocks. A damage indicator associated with the total length of cracks is proposed for a complete damage evaluation. Monte Carlo simulations are used for estimating the confidence interval of this indicator. Recommendations are suggested for the assessment of damage in masonry structures due to underground excavations or soil subsidence.